Analisis Pelaksanaan Pendidikan Pranikah di Kabupaten ‎Ponorogo Tahun 2020‎ - Neneng Uswatun Khasanah; Andini Rachmawati; Ria Rahmawati (TSAQAFAH, 2021)
ABSTRACTOne of the important roles of a harmonious marriage and household is in bearing and educating future generations. And, in this case education is needed so that these goals can be carried out properly. In order to implement the expected education, policies regulated by the government are also needed. For this reason, the government, with various considerations has issued the regulations related to the non-formal education that is called by pre-marriage courses. And, that regulation can be used as a guide in conducting pre-marriage courses. This research uses field research method which are qualitative descriptive with data collection that can indicate the realization of ideas and regulation. As for the result of this research, it shows that the Ministry of Religion in Ponorogo Regency in collaboration with the Office of Religious Affairs has been consistent in implementing pre-marriage courses even though they face various obstacles starting from 2008 to the present. In addition, the existence of this pre-marriage course proves the government’s contribution in helping to reduce the divorce rate at a young age.Keywords: Pre-Marriage Education, Implementation and Evaluation, Ponorogo Regency  ABSTRAKSalah satu peran penting pernikahan dan rumah tangga yang harmonis adalah dalam melahirkan dan mendidik generasi masa depan. Dan, dalam hal ini pendidikan sangat dibutuhkan agar tujuan tersebut dapat terlaksana dengan baik. Agar terlaksananya pendidikan yang diharapkan ini, dibutuhkan pula kebijakan-kebijakan yang diatur oleh pemerintah setempat. Untuk itu, pemerintah dengan berbagai macam pertimbangan telah mengeluarkan aturan terkait pendidikan non formal yang dibungkus dalam bentuk kursus pra nikah. Peraturan pemerintah ini dapat dijadikan pedoman dalam menyelenggarakan kursus pra nikah. Penelitian ini menggunakan metode penelitian lapangan (field research) yang bersifat deskripstif kualitatif dengan pengumpulan data yang dapat menunjuk realisasi suatu gagasan, ide dan peraturan. Adapun hasil penelitian menunjukkan bahwasannya Kemenag Kabupaten Ponogoro bekerjasama dengan Kantor Urusan Agama telah konsisten dalam melaksanakan kursus pra nikah walau dihadapkan berbagai macam kendala terhitung dari tahun 2008 hingga sekarang. Disamping itu, dengan adanya kursus pra nikah ini membuktikan adanya kontribusi pemerintah dalam membantu menekan angka perceraian di usia muda.Kata Kunci: Pendidikan Pra Nikah, Pelaksanaan dan Evaluasi, Kabupaten Ponorogo.